Analisis Pengaruh Motivasi Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada PT Kurnia Putra Mandiri Medan - Dennis Widjaja; Martinus Tjendana; Anton Ng; Rezeki Ongsa (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2022)
The population in this study were employees of PT. Kurnia Putra Mandiri Medan, totaling 65 people. All members of the population are used as a unit of analysis or population research. And the results of this study indicate that Motivation (X1) has a positive and significant effect on Employee Work Performance (Y), this is evident from the results obtained that the t-count value for the X1 variable (Motivation) is 6.520 while the t-table is 0.678. So 6.520 > 0.678, because t-count is greater than t-table, then H0 is rejected and H1 is accepted and it can be concluded that Motivation (X1) has an influence on Employee Performance. Job Satisfaction (X2) has a positive and significant effect on Employee Work Performance (Y), this is evident from the results obtained that the t-count value for the X2 variable (Job Satisfaction) is 2.401 while the t-table is 0.993. So 2.401 > 0.993, because t-count is greater than t-table, then H0 is rejected and H2 is accepted and it can be concluded that Job Satisfaction (X2) has an influence on Employee Performance (Y). Meanwhile, the variables Motivation (X1) and Job Satisfaction (X2) have a positive and significant effect together on Employee Work Performance (Y).